Perceptions of Teacher-trainees Towards using YouTube Videos to improve Conceptual Understanding of the Reactivity of Alkali Metals in Natural Sciences at a Rural University in South Africa - Vuyokazi Momoti (E-Journal of Humanities, Arts and Social Sciences)
YouTube videos are frequently used in educational settings to improve students’ academic performance. This study investigated the impact of YouTube on acceptance and usability using the Technology Acceptance Model (TAM) at a rural university in South Africa. The focus of the research was to understand the perspectives of teacher candidates regarding the significance of YouTube in enhancing their understanding of laboratory safety and alkali metal reactivity. YouTube videos have been found to be essential for comprehending scientific experiments due to their visual components, detailed explanations, user-friendly interfaces, interactivity, and ability to simplify complex ideas. They complement traditional teaching methods, encourage social interaction, and stimulate curiosity and innovation across different age groups. The survey involved 32 teacher candidates enrolled in a Natural Science class, with five questionnaires not returned. The survey’s reliability was confirmed with a Cronbach alpha value of 0.710 during testing. Descriptive statistics were utilized to analyse the data, determining the mean and variability. The research indicates that future educators highly prefer using YouTube to learn about Natural Science experiments and are open to integrating technology for educational purposes. Therefore, the research may improve the understanding of theoretical scientific procedures by encouraging educators to advocate for the use of digital resources in education, ultimately enhancing academic achievements. The findings of this research will enhance understanding of the importance of utilizing YouTube to support student learning. Educators can leverage this information to develop effective strategies for enhancing student learning by understanding what drives students to use YouTube for educational purposes.